Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pelayanan Pada PT. Jalur Nugraha Ekakurir Cabang Kalabahi Kabupaten Alor - Siti Sunarti Arsat (Jurnal Ilmiah Wahana Pendidikan, 2023)
This Research Purposes To Know The Influence Of The Dimensions Of Service Quality On Customer Satisfaction Pt JneKalabahi Branch, Alor Regency This type of research Is a Quantitative Research With Data Collection Techniques Namely Observation Questionnaires, Interviews, and Documentation Studies This Research Uses Data Primary. The population in this study are all customers at Pt Jne Branches Kalabahi and the sampling technique in this study are coincidental Sampling Then the sample in the study is the customer at Pt Jne Branch Kalabahi, totaling 30 people who were used as samples in this study The statistical method used in this research is linear regression Multiplied By Seeing The Significant Value Of The T Test And The Significant Value Of The F Test As Reject Ukuư In Taking Hypotheses. The results of this study show Babwa: (1), Partially Physical Evidence Variables Choose a Significance Value of 0.004 or 0.4% Where This Value Is Smaller From the alpha value, which is 0.05 or 59%, the results of this research are acceptable. H1 which Stating that the Physical Evidence Variable has a Partial Positive Effect. Against Customer Satisfaction at Pt Jne Kalabahi Branch (2). Partially The Reliability Variable Has a Significant Value of 0.003 or 0.3% where This value is smaller than the alpha value, which is 0.05 or S%, so the research results Inn Accepts H2 Which states that the reliability variable is partial Positive Influence on Customer Satisfaction at Pt JneKalabahi Branch (3) Partially the responsiveness variable has a significant value of 0.017 or 1.7% where this value is smaller than the alpha value which is 0.05 or 5% so The results of this study accept H3 which confirms that the responsiveness variable Partially Has a Positive Influence on Customer Satisfaction Jne. Kalabahi Branch (4). Partially Guarantee Variables Have Value Significant 0.037 or 3.7% where this value is smaller than the alpha value That is equal to 0.05, namely 5% so that the results of this researcher are partially accepted H4 which states that the guarantee variable partially has a positive effect Against Restricted Customer Satisfaction at Pt Jne Kalabahi Branch (5) in a manner Partial Empathy Variable Has A Significant Value Of 0.018 Or 1.8% Where This value is smaller than the alpha value, H5 which is equal to 0.05, which is 5% so that the results This Research Partially Empathy Variable Has a Positive Influence on Satisfaction Customers at Pt Jne.cabang Kalabahi. So that the results of this research are partial Accepting Language Stating That Guarantee Variables Are Partially Influential Positive Against Customer Satisfaction at Pt JneKalabahi Branch (6). Simultaneously Variables Physical Evidence, Reliability, Responsiveness, Assurance, And Empathy has a significant value of 0.000 or 0.0%, where is this value Smaller than the alpha value, which is equal to 0.05, which is 5%, so the research results It partially accepts H6 which states that the physical evidence variable Reliability, Responsiveness, Ja 4 Assurance, And Empathy Simultaneously E Positive Against Customer Satisfaction at PT. Jne Kalahahi